2012
DOI: 10.1017/s1368980012001310
|View full text |Cite
|
Sign up to set email alerts
|

The association between dairy food intake and the incidence of diabetes in Australia: the Australian Diabetes Obesity and Lifestyle Study (AusDiab)

Abstract: Objective: Several studies have suggested that dairy food may reduce the risk of obesity and metabolic abnormalities but few have been able to conclusively demonstrate that it reduces the risk of diabetes. The aim of the present analysis was to investigate if dairy food intake independently reduces the risk of diabetes. Design: The Australian Diabetes Obesity and Lifestyle Study (AusDiab) is a national, population-based, prospective survey conducted over 5 years. Baseline measurements included a 121-item FFQ, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
3
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 25 publications
4
38
3
2
Order By: Relevance
“…These associations among Chinese populations seemed stronger than those from a previous meta-analysis, which showed that the risk of type 2 diabetes was 14% lower in the highest quintile of total dairy consumption compared with the lowest quintile (5,35). Several recent studies, on the other hand, did not find significant associations between dairy product consumption and diabetes (8)(9)(10)(11)(12). For example, Sluijs et al (10) showed that the RR (95% CI) for type 2 diabetes comparing extreme quintiles of total dairy consumption was 0.97 (0.82-1.15, P = 0.69) by pooling case-cohort samples from eight countries in the European Prospective Investigation into Cancer and Nutrition study (10,694 participants with incident type 2 diabetes and 13,780 in the subcohort).…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…These associations among Chinese populations seemed stronger than those from a previous meta-analysis, which showed that the risk of type 2 diabetes was 14% lower in the highest quintile of total dairy consumption compared with the lowest quintile (5,35). Several recent studies, on the other hand, did not find significant associations between dairy product consumption and diabetes (8)(9)(10)(11)(12). For example, Sluijs et al (10) showed that the RR (95% CI) for type 2 diabetes comparing extreme quintiles of total dairy consumption was 0.97 (0.82-1.15, P = 0.69) by pooling case-cohort samples from eight countries in the European Prospective Investigation into Cancer and Nutrition study (10,694 participants with incident type 2 diabetes and 13,780 in the subcohort).…”
Section: Discussioncontrasting
confidence: 64%
“…However, only some prospective studies have observed inverse associations between dairy consumption and risk of diabetes (5-7), whereas others reported null findings (5,(8)(9)(10)(11)(12). In this regard, prospectively investigating associations between dairy consumption and cardiometabolic traits related to diabetes may shed light onto the relationship between dairy consumption and risks of diabetes.…”
mentioning
confidence: 99%
“…When studies reported conversion factors, these factors were applied (14,18,19,28). For several studies (13,15,(19)(20)(21)(22)24) additional data were provided by the authors or coworkers. There were overlapping data for 2 studies, namely, the European Prospective Investigation into Cancer and Nutrition (EPIC)-InterAct (22) and EPIC-Norfolk (12).…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%
“…The sample size of the cohorts ranged from 640 to 85,884, and the duration of follow-up ranged from 2.6 to 30 y. Nine studies were conducted in the United States (4,14,17,19,21,25,26), 8 in Europe (10-13, 20, 22-24), 3 in Asia (16,27,28), and 2 in Australia (15,18). The dairy foods studied and definitions of dairy categories differed across studies, as described in Supplemental Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation